HONG KONG AND NEW ZEALAND LEARNING ASSESSMENT SYSTEM (Literature Study and Inspiration for Learning Assessment of Islamic Religious Education in Indonesia) - Moh. Rifqi Rahman; Bassam Abul A'la (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2022)
The learning assessment process is still an interesting discussion theme, especially with the presence of the term AfL (Assessment for Learning) which is a development of the AoL (Assessment of Learning) concept. The purpose of this article is to describe the implementation of AfL in two different regions, Hong Kong and New Zealand with the indication that there are several studies showing that AfL is running well in these two regions. The results of the description are then linked to the context of the assessment of Islamic Religious Education learning in Indonesia today. This research is a literature study with a qualitative model that begins with the search for sources (heuristics), assessment (criticism) and construction. As a result, Hong Kong presents an assessment system in the form of BCA (Basic Competency Assessment) and SBA (School-Based Assessment); while New Zealand implemented several policies to strengthen the implementation of this AfL. When referring to the implementation of AfL in the two regions, Indonesian Islamic Education requires teachers who are prepared and competent in carrying out the assessment. The Islamic Religious Education assessment system is very detailed and clear, but teachers are still not able to apply it.